Levetiracetam: an open label study on safety and efficacy in newly diagnosed partial onset seizures as monotherapy - R.S., Jacob Jesurun; K., Manimekalai; G., Somasundaram; R., Subash K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The Common neurological disorder in pediatric population is epilepsy. Despite having many medications and with recent approval of levetiracetam (LEV) as an adjunctive treatment in children, there is a need to evaluate safety and efficacy of this drug in Indian population. The aim was to study the efficacy and tolerability of levetiracetam as monotherapy, in newly diagnosed partial onset seizures. Methods: Newly diagnosed partial seizure patients attending the neurology outpatient department were considered for the study based on the inclusion criteria. After the patients were started on the minimal therapeutic dose of the allocated drug LEV 500 mg twice daily over a period of 2 weeks, if there is no adequate seizure control, the dose of medication was further stepped up. Dose level 2 was taken as 1000 mg twice daily for levetiracetam over next 2 weeks. Dose level 3, 1500 mg twice daily for levetiracetam for the final 2 weeks (Maximum dose tried). After 6 weeks of dose stabilization, all patients had a final evaluation at the end of 6 months to assess for 6 month seizure free period. Results: Out of 37 subjects who had first visit eligibility on screening 5 did not give consent 2 were in exclusion criteria with 30 involved in study three were lost in follow up. Among 28 children in levetiracetam group 17 (62.96%) had seizure control at 6 months with dose level 1 (20 mg/kg/day) itself. 8 patients (25.92%) had control on dose level 2 (30 mg/kg/day). 2 patients (7.40%) had seizure control at maximum dose level 3 (40 mg/kg/day). In 1 patient, seizures were not controlled in spite of maximum dose. This patient was started on alternative drugs. The commonest discomfort faced by the subjects include nausea 14 (51.85 %), drowsiness 11 (40.74%), unsteadiness 6 (27%), diplopia 6 (20%) and headache 6 (20%). Conclusions: Though the present study is an analysis of small population and open labeled, the results are clear levetiracetam as monotherapy is effective in majority of study population at a dose of 20 to 40 mg/kg/day. The cost effectiveness and safety of the drug has also given promising results for its usage among pediatric age group. A study on large group with comparison to existing gold standard drugs with proven efficacy in children like gabapentin, topiramate, oxcarbazepine and lamotrigine can give more information as monotherapy and its use as adjunctive drug.